2022
DOI: 10.1055/s-0042-1743451
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Laparoscopic Posterior Mesh Rectopexy for Complete Rectal Prolapse: A Case Series with Review of Literature

Abstract: Background Trans-abdominal rectopexy for complete rectal prolapse (CRP) reportedly yields more definitive results as compared with trans-perineal surgery. In the era of minimal access surgery, minimally invasive laparoscopic rectopexy has become a popular treatment option for patients with rectal prolapse (RP). Herein, we describe our preferred surgical procedure for the correction of RP and evaluate its results. We further aim to perform a comparative assessment between perioperative outcomes achieved with op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In Chawda & Joshi study, which assessed the demographic features of all the 14 study subjects who presented with RP; they observed that the mean age of the subjects was 48.42 years .There was a male preponderance observed in this study, which is against a well established female preponderance in the disease. The observed M:F ratio was 1.8:1 (14) . As regard operative time; it was shorter in mesh rectopexy group than in resection rectopexy .…”
Section: Discussionmentioning
confidence: 84%
“…In Chawda & Joshi study, which assessed the demographic features of all the 14 study subjects who presented with RP; they observed that the mean age of the subjects was 48.42 years .There was a male preponderance observed in this study, which is against a well established female preponderance in the disease. The observed M:F ratio was 1.8:1 (14) . As regard operative time; it was shorter in mesh rectopexy group than in resection rectopexy .…”
Section: Discussionmentioning
confidence: 84%